Disaster Risks and Mitigation in The Tanjung Lesung Special Economic Zone: The Role of The Banten Provincial Government, The Pandeglang Regency Government, and PT Banten West Java - Sebastian Pardamean (PT Publikasiku Academic Solution, 2026)
The Tanjung Lesung Special Economic Zone (SEZ) is one of Indonesia’s strategic tourism development areas; however, its coastal location in the Sunda Strait exposes the region to significant disaster risks, particularly tsunamis, earthquakes, flooding, and coastal abrasion. The 2018 Sunda Strait tsunami demonstrated the vulnerability of tourism infrastructure and highlighted the importance of strengthening disaster mitigation governance to support sustainable regional development. This study aimed to examine disaster risks and mitigation strategies in the Tanjung Lesung SEZ, focusing on the roles and coordination of the Banten Provincial Government, Pandeglang Regency Government, and PT Banten West Java as the development and management entity. This research employed a qualitative approach with an interpretive paradigm using a single-case study design. Data were collected through document analysis of government policies, development plans, disaster management documents, implementation reports, and relevant scientific literature. The findings indicated that although disaster mitigation instruments, including disaster risk zoning, environmental management frameworks, and resilience policies, had been established, their implementation remained suboptimal due to fragmented authority and limited inter-organizational coordination. The provincial government contributed through strategic coordination, the regency government managed local disaster preparedness, and PT Banten West Java supported infrastructure recovery and ecosystem-based mitigation initiatives. However, challenges remained in early warning systems, evacuation infrastructure, and collaborative governance mechanisms. This study concluded that strengthening cross-sector collaboration and integrating disaster mitigation strategies into regional development planning were essential to improving the resilience and sustainability of the Tanjung Lesung SEZ.